Influence of foliar spray and post-harvest treatments on head yield, shelf-life, and physicochemical qualities of broccoli - Tarafder, Sushanta Kumar; Biswas, Mrityunjoy; Sarker, Umakanta; Ercisli, Sezai; Okcu, Zuhal; Marc, Romina Alina; Golokhvast, Kirill S. (Frontiers in Nutrition, 2023)
Rapid senescence is the key factor in the deterioration of post-harvest shelf-life in broccoli heads. This study evaluates the head yield and its related traits, and physicochemical attributes of broccoli under four foliar sprays of mineral nutrients (B, Zn, Mo, and B + Zn + Mo) with control. The interaction effects of shelf-life and physicochemical attributes of broccoli for these five preharvest and five post-harvest storage treatments (LDP bag, HDP vacuum pack, 2% eggshell powder solution, 2% ascorbic acid, and control) both at cold storage and room temperature were evaluated with three replications. The significantly higher marketable head yield of 28.02 t ha-1, maximum gross return [(Bangladesh Taka (BDT 420300 ha-1)], net return (BDT 30565 ha-1), and maximum benefit-cost ratio (BCR) of 3.67 were obtained from the pre-harvest foliar application of B + Zn + Mo in broccoli. Pre-harvest foliar spray of combined nutrient B + Zn + Mo and post-harvest treatment high-density polyethylene (HDP, 15 μm) vacuum packaging efficiently improve post-harvest physicochemical attributes viz. compactness, green color, texture, carbohydrates, fats, energy, antioxidants, vitamin C, and total phenols in broccoli head compared to the rest of the treatment combinations. In addition, this treatment combination also confirmed a maximum shelf-life of 24.55 days at cold storage [relative humidity (RH) 90-95% and 4 °C] and 7.05 days at room temperature (RH 60-65% and 14-22 °C) compared to the rest of the treatment combinations. Therefore, we recommend a pre-harvest foliar spray of combined nutrient elements B + Zn + Mo and an HDP (15 μm) vacuum post-harvest packaging for the maximum benefits for both farmers and consumers to get the best head yield, anticipated physicochemical attributes, and maximum shelf-life of broccoli.